Internal arcing and lightning strike damage in short carbon fiber reinforced thermoplastic composites. (5th January 2021) - Kumar, Vipin; Yeole, Pritesh S.; Hiremath, Nitilaksha; Spencer, Ryan; Billah, Kazi Md Masum; Vaidya, Uday; Hasanian, Mostafa; Theodore, Merlin; Kim, Seokpum; Hassen, Ahmed Arabi; Kunc, Vlastimil
Abstract: Short carbon fiber reinforced thermoplastic composites (S-CFRTP) are currently used in interior parts of aircraft such as electronic circuitry and assemblies, and their usage in aircraft's exterior is also being studied. A lightning strike study on S-CFRTPs is presented in this paper. High performance thermoplastics such as a polyphenylene sulfide (PPS) reinforced with 50% weight (wt.) short carbon fiber (CF), a polyphenyl sulfone (PPSU) reinforced with 25 % wt. Short CF and a acrylonitrile butadiene styrene (ABS) with 20 % wt. short CF were tested against artificial lightning strikes. All samples were prepared using an extrusion compression molding (ECM) technique. A modified component A (100 kA) of lightning waveform, as defined by SAE ARP 5412-B, was applied. High speed imaging, thermography, scanning electron microscopy (SEM) and ultrasonic non-destructive evaluation were performed to understand the effect of lightning strikes on the thermoplastic panels. The results show that electrical conductivity of the composite, thermal stability of the polymers, and CF orientation significantly affected the damage from artificial lightning strikes. PPS composite had the highest resilience against lightning strike damage, retaining 95% and 89% residual flexural strength and modulus, respectively. CF exfoliation due to internal arcing was observed in the carbon fiber-reinforced ABS polymer (CF-ABS) composite. CF exfoliation damage has been reported for the first time. Graphical abstract: Image 1